Lifting the Fog in Endoscopic Surgery - Legeros, Jan (Operating Room Nurses Association of Canada Journal, 1998)
This article describes a problem encountered in addressing the phase out of CFCs, the subsequent reduction in the use of the low temperature sterlization modailities and the move towards greater utilization of steam sterilization. The ban of CFCs drastically changed the way reprocessing of sterile supplies and equip- ment is performed in Hospitals. In 1994 at St. Boniface General Hospital Operating Room in Winnipeg, Manitoba, preparations began to meet the challenge. One of the measures taken was to review purchases for new equipment and where ever possible, choose equipment that could be sterilized using steam as opposed to using Ethylene Oxide sterlization. Medical device companies responded to the CFC ban by modifying the manufacture of delicate equipment to withstand the high temperatures used in steam sterilization. Equipment such as rigid telescopes could be steam sterilized for the first time.